Penggunaan Metode Analytic Network Process (ANP) Untuk Pendukung Keputusan Pemberian Bonus Karyawan - Nadia Ulfa; Muhammad Arhami; Muhammad Rizka (Politeknik Negeri Lhokseumawe, 2021)
The decision support system is a system that can provide problem-solving abilities and communication skills for problems with semi-structured and unstructured conditions, such as determining which employees deserve a bonus. The decision-making process is a frequent occurrence and is at the core of activities at PT Perta Arun Gas, one of which is to determine bonuses for employees by calculating the average value of criteria for each employee, not counting the values of related criteria. The system designed is a decision-making system to determine employees who get bonuses using the Analytic Network Process (ANP) method, this ANP method can calculate the related criteria values. ANP is a method that accommodates the relationship between criteria and alternatives. The criteria used are, professional at work, politeness (behavior), presence, loyalty (a sense of ownership of employees towards the company), responsibility, cleanliness tidiness, and discipline. The test results indicate that this system can solve the problem of determining the distribution of bonuses to employees so that it can help in selecting employees who receive the bonus.